Pengaruh Mechanical Cleaning dan Heat Treatment Komposit Nikel-Grafit Hasil Thermal Spray Coating Terhadap Bond Strength dan Kekerasan pada Substrat Baja AISI 321 - Prajitno, Djoko Hadi (ROTASI, 2020)
Thermal spray coating (TSC) is one of the coating methods to prevent direct interaction between the surface of the substrate and the operating environment, which has the potential to degrade the function and lifetime of the component or even the system as a whole. In this study, an investigation of Ni-Al coating quality as a bondcoat and Ni-C as a topcoat on AISI 321 Steel substrate with 3 variations of the treatment of the specimen. Variation of treatment (treatment) ie the first specimen is directly tested for bond strength, while the second specimen is given heat treatment and the third specimen is subjected to mechanical cleaning. Both substrate, bond coat and top coat are characterized by testing bond strength, hardness, microstructure and chemical composition. Bond strength test results are 2042-5404 psi for specimens with heat treatment, 597-731 psi for specimens with mechanical cleaning, and 842 psi for specimens of thermal spray results, while the hardness value is 261-308 HVN for top coat, 333-HVN for specimens with mechanical cleaning, and 195-240 HVN for specimens with heat treatment.